مقارنة الصفات الشكلية لأنواع من جنس Euphorbia (Euphorbiaceae) وإضافة E. serpens Kunth للفلورا السورية . - حداد دينا (Latakia University Journal -Biological Sciences Series, 2017)
شملت هذه الدراسة مقارنة صفات شكلية / للنورة السيتونة وعدد وأنماط الغدد – سطح الثمرة – سطح البذرة- الأوبار - الحليمات / لدى 10 أنواع تابعة لجنس Euphorbia ( الحليبة ) هي: E.prostrata , E. serpens , E.pilulifera , E.geniculata , E. thamnoides E. helioscopia , E. aleppica , E. peplus , E. terracina , E. paralias، وأوضحت أن الغدد اختلفت بالعدد والشكل بين غدة وحيدة قمعية عند نوع واحد أما بقية الأنواع امتازت بوجود 4 غدد منها ما كان مؤلف من قطعتين، أو بيضوية قرصية الشكل الى مستطيلة مع وجود تسننات على حافتها، أو منجلية . بالنسبة لسطح الثمرة امتاز بوجود أوبار عليها بالكامل، أو على حافة الكرابل فقط، و بعضها كان له زوائد بشكل أجنحة عند حدود الكرابل، أوزوائد مخروطية على كامل سطحها وأنواع امتازت بسطح أملس أو خشن محبحب . أما البذور تميزت بسطح خشن أو مجعد، أو أملس أو شبكي أو محفر أومبقع بدوائر مسودة . أماالأوبار فكانت إما متعدد الخلايا أو وحيدة الخلية أو عديمة الحواجز، والحليمات أيضأً كانت 3 أنماط إما كروية أوهرمية أو بشكل قبة . ومن أبرز النتائج كان تسجيل النوع : Euphorbia serpens Kunth كإضافة للفلورا السورية. The study focused on the comparison of the morphological characteristics of the studied species in term of cyathium inflorescence, pattern and number of glands , fruit surface, seed surface, Trichomes and papillae of 10 species of the genus Euphorbia : E.geniculata , E.pilulifera, E. serpens, E.prostrata, E. thamnoides E. helioscopia , E. aleppica , E. peplus , E. terracina , E. paralias . Glands differed in number and shape between mono funnel gland in only one species, while have 4 glands in the others. Some of glands consist of 2 parts, or have oval-rectangular shape with dentate on the edge, or sickle. carple Surfaces of fruit has Trichomes on the all Surface or just on the edge of carple, some of surfaces have growth like wings on the edge of the carple, or conical shape on all surface, and some species have smooth shape or rough-grained. Seeds have Surfaces:rough,curly,smooth,reticulate,pittedor dotted. There is tow types of Trichomes: mono or multi-cells or Aseptate flagellate . Papillae have pyramidal or spherical shapes or dome . The most notable results were recording one specie: Euphorbia serpens Kunth As an addition to the Syrian flora.